Comparative Analysis of Chemical Composition and Antioxidant Activity in Conventional, Civet, and Elephant Coffees: Is There a Definitive Authentication Marker of Elephant Coffee? - Jan Hájíček; Gökçe Hoca; Matúš Várady; Petr Maršík; Adéla Fraňková; Jan Tauchen (Beverages)
Novel methods of coffee processing, including animal-assisted fermentation, are gaining popularity—among them, elephant dung coffee stands out for its rarity and high price, making it a likely target for adulteration. This study aims to discover candidate biomarkers for elephant coffee by comparing the chemical composition, antioxidant activity, and volatile profiles of Arabica coffee processed by three methods: conventional, civet-derived, and elephant-derived (all originated from Southeast Asia, medium roast). Analytical methods included HPLC-UV and GC-SPME-MS, along with in vitro antioxidant assays (DPPH, ORAC, ABTS, total phenolics, and total flavonoids). Principal Component Analysis (PCA) was used to evaluate differences between the samples. While elephant coffee showed lower caffeine (0.93%) and antioxidant capacity across all assays, it was richer in selected volatile compounds, such as pyrazines (e.g., 3-ethyl-2,5-dimethylpyrazine; 3.73% RPA), 2- and 3-methybutanal (1.18 and 0.19% RPA), and furfuryl acetate (18.00% RPA; p < 0.05). These changes are likely to be due to fermentation in the gastrointestinal tract. Despite differences, no definitive biomarker of elephant coffee was found, suggesting that discrimination from other coffee samples may not be as simple as previous studies indicated. More studies with a higher number of samples that employ an extensive analytical approach (e.g., omics or NMR) to thoroughly analyze the phytochemical profile of coffee beans before and after digestion by the elephant are needed.